Paradoxical Presentation In A Case of Deep Frontal Lobe Abscess - TS, Vasan; Mathur, Karan; Vyas, Rahul (Archives of Clinical and Medical Case Reports, 2020)
A pyogenic brain abscess may start initially with cerebritis and later develop a capsule and a necrotic centre thus, forming an abscess. A pyogenic abscess is not uncommon and can be due to a multitude of organisms. It may occur due to spread from a contiguous focus, haematogenous spread or head trauma etc. We report here, a case with no detectable source of infection in a case with a left to right shunt patent foramen ovale (PFO). Such a shunt is an unusual presentation as only a right to left shunt is known to bypass the pulmonary filter and lead to seeding, in the absence of a coexisting pulmonary arteriovenous malformation.